Respuestas
Respuesta dada por:
3
3x + x² = 88
x² + 3x - 88 = 0
![x = \frac{-3 +- \sqrt{9+352} }{2} x = \frac{-3 +- \sqrt{9+352} }{2}](https://tex.z-dn.net/?f=x+%3D+%5Cfrac%7B-3+%2B-+%5Csqrt%7B9%2B352%7D+%7D%7B2%7D+)
![x = \frac{-3 +- \sqrt{361} }{2} x = \frac{-3 +- \sqrt{361} }{2}](https://tex.z-dn.net/?f=x+%3D+%5Cfrac%7B-3+%2B-+%5Csqrt%7B361%7D+%7D%7B2%7D+)
![x = \frac{-3 +- 19 }{2} x = \frac{-3 +- 19 }{2}](https://tex.z-dn.net/?f=x+%3D+%5Cfrac%7B-3+%2B-+19+%7D%7B2%7D+)
x1 = (-3 + 19) : 2 = 16 : 2 = 8
x2 = (-3 - 19) : 2 = -22 : 2 = -11
Las dos posibles respuestas son 8 y -11
x² + 3x - 88 = 0
x1 = (-3 + 19) : 2 = 16 : 2 = 8
x2 = (-3 - 19) : 2 = -22 : 2 = -11
Las dos posibles respuestas son 8 y -11
Preguntas similares
hace 6 años
hace 6 años
hace 6 años
hace 9 años
hace 9 años